2009
DOI: 10.1039/b910924b
|View full text |Cite
|
Sign up to set email alerts
|

Improving PEM fuel cell catalyst activity and durability using nitrogen-doped carbon supports: observations from model Pt/HOPG systems

Abstract: This study presents clear and compelling experimental evidence for the significant beneficial effects of nitrogen-doping on the activity of Pt/C catalyst systems for the methanol oxidation reaction. This evidence is obtained through the deployment of geometrically well-defined model catalytic systems consisting of tunable assemblies of Pt catalyst nanoparticles deposited onto undoped, Ar-doped, and N-doped highly oriented pyrolytic graphite (HOPG) substrates. Both Ar-and N-doping were achieved via ion beam imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
174
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(181 citation statements)
references
References 31 publications
7
174
0
Order By: Relevance
“…Third, nitrogen doping results in an improvement in hydrophilicity and wettability of CNx. 52 The enhanced access of solvated and charged PtCl 6 2-ions to the CNx surface can be associated with the superior dispersion of Pt nanoparticles and the avoidance of agglomeration. It is found that CNx is easier to disperse in the solution during experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Third, nitrogen doping results in an improvement in hydrophilicity and wettability of CNx. 52 The enhanced access of solvated and charged PtCl 6 2-ions to the CNx surface can be associated with the superior dispersion of Pt nanoparticles and the avoidance of agglomeration. It is found that CNx is easier to disperse in the solution during experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen-doped carbon (CN x ) with noble metallic nanoparticles deposited on its surface exhibited an enhanced catalytic activity toward ORR as the CN x had greater electron mobility and showed n-type or metallic behavior [17][18][19][20][21]. Doping nitrogen into graphite has significant effects on both the morphology and electrocatalytic behavior of Pt nanoparticles [22]. If CN x can form on the surface of Fe 3 O 4 , this new material could be a new desirable catalyst support for electrocatalysts, since Pt will exhibit a good durability on the support surface due to anchoring from nitrogen incorporation [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of nitrogen into carbon supports has showed to improve durability, as well as enhancing the intrinsic catalytic activity for both oxygen reduction (ORR) and methanol oxidation (MOR) reactions (41)(42)(43)(44)(45)(46)(47)(48). The N-dopant has been reported to alter the catalyst electronic structure, resulting in a higher binding energy, which may decrease the specific interaction between the Pt nanoparticles and potential poisoning intermediates (49).…”
Section: Introductionmentioning
confidence: 99%